Feasibility Study of Physician Orders for Life-Sustaining Treatment for Patients with Terminal Cancer - An, Ho Jung (Cancer Res Treat, 2019)
PURPOSE: Physician Orders for Life-Sustaining Treatment (POLST) form is a legal document for terminally ill patients to make medical decisions with physicians near the end-of-life. A multicenter prospective study was conducted to evaluate the feasibility of POLST administration in actual oncological practice. MATERIALS AND METHODS: Patients with terminal cancer, age ≥ 20 years, and capable of communicating were eligible. The primary endpoint was the completion rate of POLST. Data about physicians’ or patients’ barriers were also collected. RESULTS: From June to December 2017, 336 patients from seven hospitals were eligible. Median patient age was 66 years (range, 20 to 94 years); 52.7% were male; and 60.4% had poor performance status. Primary cancer sites were hepato-pancreato-biliary (26.2%), lung (23.2%), and gastrointestinal (19.9%). Expected survival duration was 10.6±7.3 weeks, with 41.2% receiving hospice care, 37.9% showing progression after cancer treatment, and the remaining patients were under active treatment (15.8%) or initially diagnosed with terminal cancer (5.1%). POLST forms were introduced to 60.1% of patients, and 31.3% signed the form. Physicians’ barriers were reluctance of family (49.7%), lack of rapport (44.8%), patients’ denial of prognosis (34.3%), lack of time (22.7%), guilty feelings (21.5%), and uncertainty about either prognosis (21.0%) or the right time to discuss POLST (16.6%). The patients’ barriers were the lack of knowledge/understanding of POLST (65.1%), emotional discomfort (63.5%), difficulty in decision-making (66.7%), or denial of prognosis (14.3%). CONCLUSION: One-third of patients completed POLST forms, and various barriers were identified. To overcome such barriers, social engagement, education, and systematic support might be necessary.